Çağdaş sanatta anlatım öğesi olarak büyüsel ritüeller - Kılıçarslan, Kerim (My University, 2000)
Like all branches of Turkish art, on pressuring on to fabric has been improved and its different forms has been generated from period to period. Its colour and pattern characters are parallel of the other work of arts, too. In all of the branches, there was an unity of a style when the classic Ottoman art reached at the top in the XVI. century. Twisted branches, HANÇER leaves, hatâyi, rumî, power and abundance symbol: NAR, grapes; life tree that symbols eternity and eternallity; KANDİL and bird figures are reflected on pressuring on fabrics with the most lively and bright colours. Pressuring on to fabric (yazma) has given its most of specimens with the Istanbul pressuring on to fabrics in the XVII, XVIII and XIX centuries. A few pressuring on fabric's old Specimens could reached to our days, because they were used on daily life and they were not as durable as the other work of arts. Traditional handmades are proportional of request. Pressuring on fabric's usage showed various branches as clothing and home textiles in the last periods. It's sorts has reduced and it is produced as a usage material because of production technics and its usage materials in our days. Art anxiety changed to commercial circulation desiring and that's the reason of it. Like all of the other hand made arts, the pressuring on fabric went back and went, in the hesitate period because of the unsuitable conditions. There fore, the activity to live them again has been keeping on the world and our country. Bedri Rahmi Eyüboğlu, who has this idea, examined the primitive family art and went towards to pressuring on fabric that gives on importance on nakış in his work. In 1957 he set ahead his mozaik operations that swarms with kilim, nakış, yazma and as the other people handmade arts with his own original style. Bedri Rahmi Eyüboğlu and Eren Eyüboğlu consittuted a yazma WORKSHOP and produced yazmas with their own original style in Kalamış in 1950. In our time, their sons Mehmet Eyüboğlu and their brides are producing yazma with Hughette Bouffard in the same workshop. I believe that yazmacılık which was produced with the other arts in the past, must continue to be produced in its own character according to our time's art worths. The education and pratice of yazmacılık is done by our faculties which are giving art education to people about handmade arts with the aim of to searchim, continveing and developing people handmade arts. I will endeavour for the yazmacılık that I'm glad to have this education and practice.
Keywords: 1900 - 1999; Büyülü gerçekçilik (Sanat); Güzel ve dekoratif sanatlar; Sanat, Modern_1900-1999 (20. Yüzyıl); Tarihi dönemler